Luteolin normalizes Blood Pressure via its antioxidant activity and down-regulation of Renal Angiotensin II receptor and Mineralocorticoid receptor expressions in rats co-exposed to Diclofenac and Sodium Fluoride (2022)
This study was designed to investigate the modulatory role of Luteolin (Lut), a flavonoid phytochemical, on haemodynamic parameters and the potential mechanisms involving renal Angiotensin II (AT2R) and Mineralocorticoid (MCR) receptors in renal toxicity induced by co-exposure to Diclofenac (Dcf) and sodium fluoride (NaF) in rats. Male Wistar rats were administered with either vehicle (control), Dcf only (9 mg/kg orally) or concurrently with NaF (300 ppm in drinking water). Other groups were treated with LutA (100 mg/kg) or LutB (200 mg/kg) along with Dcf and NaF exposures. All treatments lasted 8 days, following which blood pressure indices were measured using tail-cuff plethysmography. Renal expressions of AT2R and MCR were studied with immunohistochemistry, while biomarkers of oxidative and antioxidant status were also measured in the kidneys. Systolic, diastolic and mean arterial pressures were significantly (p<0.05) reduced in Dcf-treated rats, compared to control values. However, co-treatment with NaF or Lut restored these parameters. While the expression of AT2R and MCR was high in the Dcf and Dcf+NaF groups, treatment with Lut caused obvious reduction in the renal expression of these receptors. Increased lipid peroxidation (Malondialdehyde) and protein oxidation (protein carbonyls)with a lowering of reduced glutathione levels contributed to the renal toxicity of Dcf, and these were significantly ameliorated in Lut-treated rats. In conclusion, the preservation of haemodynamic indices by Luteolin in the experimental rats was probably mediated by mechanisms involving down-regulation of renal expressions of AT2R and MCR, reduction of oxidative stress and an improvement of renal antioxidant status.